125 'Reward rush' for GOSH: development of a mobile augmented reality application (App) to improve patient experience at GOSH. (December 2018) - Dula, G; Seth, A; Jononis, M; Mohamedally, D; Conner, S; Priestman, W; Sebire, NJ
Abstract : Background: Attendance at the hospital may be associated with anxiety for children and siblings, especially when waiting and moving around the hospital. Augmented reality (AR) apps are immersive experiences which may reduce anxiety in such scenarios. Aim: The aim of this study was to create a mobile interactive 'Pokemon-go-like' augmented reality app that would improve the patient experience when children and families visit GOSH. Methods: We developed a cross-platform mobile AR game, 'Reward Rush', using a range of tools including Vuforia and Unity for front-end object recognition and AR interface, in addition to the use of web service APIs and dreamlo database for leader board scores. Results: We demonstrate a working prototype of the Reward Rush AR app with object identification working in the live environment of the GOSH hospital reception and common areas. In addition to object recognition and AR animation, we demonstrate timer and scoring functions in addition to leader board functionality. Additional work is required to extend the number of objects, add high-quality AR graphical objects and add the ability for easy extensibility for future areas and objects. Conclusion: AR apps have significant potential to transform healthcare organisations, particularly those focused on the care of children. We demonstrate feasibility of rapidly building a customised app which can be extended across other areas and easily adapted for other organisations. Further qualitative work is required to determine the extent to which AR apps can reduce patient anxiety.